2019
DOI: 10.3390/catal9121055
|View full text |Cite
|
Sign up to set email alerts
|

Highly Carbon-Resistant Y Doped NiO–ZrOm Catalysts for Dry Reforming of Methane

Abstract: Yttrium-doped NiO-ZrO m catalyst was found to be novel for carbon resistance in the CO 2 reforming of methane. Yttrium-free and -doped NiO-ZrO m catalysts were prepared by a one-step urea hydrolysis method and characterized by Brunauer-Emmett-Teller (BET), TPR-H 2 , CO 2 -TPD, XRD, TEM and XPS. Yttrium-doped NiO-ZrO m catalyst resulted in higher interaction between Ni and ZrO m , higher distribution of weak and medium basic sites, and smaller Ni crystallite size, as compared to the Y-free NiO-ZrO m catalyst af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Besides, the O 1s curve was resolved into three peaks, which are attributed to lattice oxygen (O 2− ), carbonate species (CO 3 2− ) and hydroxyl species (OH − ) [43,48]. The Zr 3d was deconvoluted into Zr 3+ and Zr 4+ species as reported elsewhere [49]. The content of each deconvoluted peak is listed in Table 2.…”
Section: Surface Properties Of Zro 2 Supported Catalystsmentioning
confidence: 92%
“…Besides, the O 1s curve was resolved into three peaks, which are attributed to lattice oxygen (O 2− ), carbonate species (CO 3 2− ) and hydroxyl species (OH − ) [43,48]. The Zr 3d was deconvoluted into Zr 3+ and Zr 4+ species as reported elsewhere [49]. The content of each deconvoluted peak is listed in Table 2.…”
Section: Surface Properties Of Zro 2 Supported Catalystsmentioning
confidence: 92%
“…The diffraction peaks at 44.5, 51.8, and 76.4 • corresponded to the Ni metal (PDF no. 04-0850) over reduced catalysts, as shown in Figure 7b, and there was no diffraction peak of NiO [57]. In addition, no obvious diffraction peak of Si species was detected on Ni-xSi/ZrO 2 catalysts, suggesting that Si was in a high dispersion or amorphous state [51].…”
Section: The Results Of Co 2 -Tpd On Ni-xsi/zro 2 Catalystsmentioning
confidence: 93%
“…44 − 46 The third peak (γ) at 600–800 °C was assigned to the NiO species in the skeleton of ZrO 2 and ZrO 2 species. 47 , 48 The proportion of three peaks on NiO–10Al 2 O 3 –ZrO 2 and NiO–ZrO 2 catalysts is shown in Table 4 . The content of the β peak was about 40% on the NiO–10Al 2 O 3 –ZrO 2 catalyst, which was higher than the one on the NiO–ZrO 2 catalyst (15%) because the NiO–10Al 2 O 3 –ZrO 2 catalyst exhibited a large pore volume and pore diameter.…”
Section: Resultsmentioning
confidence: 99%
“… 54 , 55 The peaks at about 182.3, 181.4, 180.5, and 179.3 eV are attributed to the Zr 4+ , Zr 3+ , Zr 2+ , and Zr 1+ , respectively. 47 , 56 60 The proportion of Zr 4+ and Zr 3+ is listed at Table 5 . The proportion of surface Zr 4+ on NiO–ZrO 2 and NiO–10Al 2 O 3 –ZrO 2 catalysts were 11 and 14%, respectively, which indicated that a part of Zr 4+ could be reduced to Zr 3+ after reduction on both catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation